Newton’s Ontology and Its Theological Consequences - Mostafa Shaabani; Iraj Nikseresht; Abolfazl Kiyashemshaki (پژوهشنامه فلسفه دین, 2018)
Newton’s world consists of atoms, which cause natural phenomena with their movement through vacuum. Force is another important element of Newton’s world. Newton denies the idea that gravity is an essential property of matter. This indicates his adherence to the traditional conception of substance. Moreover, it provides a reason for him to believe in divine omnipresence. Other components of Newton’s ontology are space and time. He believes in absolute space and time and that it is God who sustains space and time, with his omnipresence. Every being, including God, exists in space and time. And since absolute space and time are God’s frame of action, contemplating about nature is a way to know God. Newton believes that his philosophy rejects material philosophy and proves an intelligent Creator and his continual action in the world. The aim of this article is to present a comprehensive image of Newton’s ontology, based on an investigation into his ideas about the material world, space, time and God.